The Relationship Of Physiotherapy Services With The Compliance Level Of Elderly Patients At Running The Physiotherapy Program In Dr. Soepraoen Malang Hospital - Kasimbara, Rachma Putri; Suhernanda, Ikhtiqod; Sartoyo; Endaryanto, Agung Hadi (Poltanesa, 2022)
Based on the results of observations of researchers at dr. Soepraoen the physiotherapy services provided are not optimal, as seen from the level of patient compliance which is lacking, this is influenced by several factors, namely reliability, responsiveness, lack of empathy for the physiotherapist, plus incomplete and inadequate facilities. So this study aims to see. There is a relationship between physiotherapy services and patient satisfaction. This research was conducted at dr. Soepraoen with a sample of 85 respondents using a purposive sampling technique. The research instrument used was a questionnaire and the data was analyzed using the chi-square test with a significant level (α=0.05). The results of this study indicate that there is a relationship between physiotherapy services and patient satisfaction (p=0.000). Based on research results. It can be concluded that there is a relationship between physiotherapy services and patient compliance.